Food History on a Postcard: The twentieth century legacy of Devon and Cornwall’s local photographers - Cleave, Paul (Petits Propos Culinaires, 2013)
Today, vintage postcards are widely collected and are an important resource for social historians. As well as the countless topographical and humorous postcards associated with holidays, there were cards depicting regional foods, the sorts of delicacy presented to visitors and the tourist. In the south-west of England, particularly Devon and Cornwall, it is the cards created by the independent local photographers which capture authentic dishes and local culinary specialities.